Modele regresji liniowej dzietności rodzin względem dochodu - Roeske-Słomka, Iwona (Wydział Prawa i Administracji UAM, 1988)
In economic theories concerning a number of children in a family income plays a special role. On the one hand, it is the factor shaping all possible attitudes and behaviors (including procreation) and — on the other — it is a factor setting in motion and controlling the functioning of competition mechanisms in the sphere of behavioral processes. The article presents the results of the analysis aimed at determining general character and intensity of the influence of income on the number of children in a family. The empirical basis of the analysis was the all-Polish research into family budgets in years 1973 - 1983. The calculus of correlation and linear regression was used with respect to more homogenous subpopulations distinguished according to the features differentiating procreative behaviors such as: the length of marriage, the level of education of the head of the household, and the character and class of place of residence. It has been found that although in some cases the range of variations of a number of children in a family explainable in terms of income was considerable, on the average income explained only a small fraction of all such variations. In most part of the subpopulation the dependence of the number of children on income was statistically insignificant. In turn, in the cases where that dependence could be considered significant, it was of positive character and usually the lower the level of education of the head of the household was, the stronger that dependence became. In the light of the above results one may suggest that the material status of a family better than the status of families belonging to the same social group is correlated with a weaker function of aspects of material competition with respect to having children. Thus a better material status strengthens extra-economic motivations for having a preferred number of children.
Models of linear regression of a nomber of children in a family and income